The role of medullary dorsal horn circuits in the diurnal regulation of nociception - Zirpel, F (2024)
Circadian characteristics of pain have been described in humans and animal models, but the underlying mechanisms remain unclear. Two striking examples of pain conditions that show a circadian pattern are migraine and cluster headache. These conditions are thought to involve activation of the trigeminal system. Upon activation of trigeminal sensory terminals, nociceptive information is electrically encoded and transmitted to the brainstem, namely the medullary dorsal horn (MDH), where synaptic transmission occurs predominantly in layers I and II. Within the MDH, pain sensory information is not only relayed onto centrally projecting neurons but also shaped by a local circuit of interneurons. Evidence suggests that orofacial pain behaviour and nociceptor activity vary depending on the time of day, suggesting a role of circadian mechanisms in the regulation of trigeminal transmission. This study aimed to investigate circadian mechanisms underlying synaptic transmission of afferent trigeminal nociceptive activity at the MDH synapse.